Quantum chemical calculations of 77 Se and 125 Te nuclear magnetic resonance spectral parameters and their structural applications - Rusakova, Irina L (Magnetic resonance in chemistry : MRC, 2021)
© 2020 John Wiley & Sons, Ltd.